Multisource Evidence for Final State Hadrons in 3.7A Gev 16O–Nucleus Interactions - M. M, Mennatallah.; Osman, W.; Fayed, M. (JOURNAL OF ADVANCES IN PHYSICS, 2018)
In 3.7A GeV 16O interactions with emulsion nuclei, the shower particle multiplicity characteristics are investigated. Data are presented in terms of the number of emitted particles in both forward and backward angular zones. The dependence on the target size and emission direction is presented. The target separation of events depends on Glauber’s multiple scattering theory approaches. A decay mechanism seems to be a characteristic of the backward production. This production may be during the deâ€“excitation of the excited target nucleus, regarding the nuclear limiting fragmentation hypothesis. The forward emitted particle is due to a creation system. The target size is an effective parameter as well as the projectile size in this system, considering the geometrical concept regarded in the nuclear fireball concept. The data are simulated in the framework of the modified FRITIOF model. The multisource thermal model can predict source numbers responsible for particle production.